ANALISIS PENERAPAN PERENCANAAN PAJAK PPH 21 YANG DITANGGUNG PERUSAHAAN SEBAGAI UPAYA PENGHEMATAN BEBAN PAJAK PENGHASILAN BADAN SERTA MANAJEMEN LABA : (STUDI KASUS PADA PT AKSARA KARYA KONSULTAN) - Nur Fitri Kusumaningrum; Joned Ceilendra Saksana; Sitti Aliyah Azzahra; Ayu Sri Rahayu; Intan Permana Lestari; Ekky Noviar (Sekolah Tinggi Ilmu Ekonomi Ganesha, 2020)
Analysis of the Application of Income Tax Planning 21 Paid by the Company as an Effort to Save Corporate Income Tax Expenses and Earnings Management (Case Study of PT Aksara Karya Konsultan). Income tax 21 for employees or experts of PT Aksara Karya Konsultan uses the gross up method. This study aims to be able to minimize the amount of costs in corporate tax. So, tax planning is needed in accordance with the laws and regulations in force in Indonesia. With this method, the company ends up bearing the tax burden of employees and experts so that the annual cost burden incurred by the company is quite high. Companies are included in corporate taxpayers who have an obligation to pay taxes. In this study, researchers chose Descriptive and Case Study research methods because this research problem is still unclear or there is no suitable data about the problem to be studied. Therefore, researchers go directly to the field to explore the object of research. The use of the Gross Up method will make the amount of income tax paid greater than the Nett method because the company must take into account the taxes that must be paid by employees. The amount of income tax paid will be smaller than the Gross Up method if the company uses the Nett method because the company does not need to take into account the taxes that must be paid by employees. The Gross Up method can be more profitable